3-D habitat suitability of jack mackerel Trachurus murphyi in the Southeastern Pacific, a comprehensive study. (August 2016) - Bertrand, Arnaud; Habasque, Jérémie; Hattab, Tarek; Hintzen, Niels T.; Oliveros-Ramos, Ricardo; Gutiérrez, Mariano; Demarcq, Hervé; Gerlotto, François
Graphical Abstract: Highlights: Jack mackerel Trachurus murphyi population substantially decreased since the 1990s. Uncertainty associated to jack mackerel population structure hampers management. Temperature, productivity and oxygen data were used to build a model of habitat in 3D. We reveal temporal gaps within the global jack mackerel habitat in the South Pacific. The more likely jack mackerel population structure is a pelagic metapopulation. Abstract: South Pacific jack mackerel, Trachurus murphyi, has an ocean-scale distribution, from the South American coastline to New Zealand and Tasmania. This fish, captured by Humans since the Holocene, is nowadays heavily exploited and its population has decreased substantially since the mid-1990s. The uncertainty associated to jack mackerel population structure currently hampers management. Several hypotheses have been proposed from a single population up to several discrete populations. Still no definitive answer was given. Determining how environmental conditions drive jack mackerel distribution can provide insights on its population structure. To do so, here we performed in three steps. First, we used satellite data to develop a statistical model of jack mackerel horizontal habitat suitability. Model predictions based on interaction between temperature and chlorophyll- a match the observed jack mackerel distribution, even during extreme El Niño event. Second, we studied the impact of oxygen and show that jack mackerel distribution and abundance is correlated to oxygen over a wide variety of scales and avoid low oxygen areas and periods. Third, on the basis of the above we built a conceptual 3D model of jack mackerel habitat in the Southeastern Pacific. We reveal the presence of a low suitable habitat along the Chilean and Peruvian coast, figuratively presenting a closed door caused by a gap in the horizontal habitat at ∼19–22°S and a shallow oxycline off south-centre Peru. This kind of situation likely occurs on a seasonal basis, in austral summer but also at longer temporal scales. A lack of exchanges at some periods/seasons partially isolate jack mackerel distributed off Peru. On the other hand the continuity in the habitat during most of the year explains why exchanges occur. We conclude that the more likely population structure for jack mackerel is a pelagic metapopulation.